Praktyczne problemy stosowania art. 40 ust. 1 ustawy Prawo budowlane - Sługocka-Kołpaczyńska, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The provision of Article 40 paragraph 1 of the Polish Construction Law provides that the authority which issued the decision granting a building permit shall transfer the decision to another entity if it accepts all the conditions set out in this decision and make a statement of its right to use the property for construction purposes. The architectural and construction authority is obliged to transfer the decision when these conditions are met. The interpretation of Article 40 paragraph 1 of the Polish Construction Law seems to fully explain how the authority should transfer a decision granting a building permit. However, this rule refers only to a situation in which an existing investor voluntarily wants to transfer powers possessed by them to any other entity. Problems in the application of the provision arise when an existing investor cannot express their will. In the article I would like to present two such cases, which often become the subject of decisions of the authorities and in respect of which settlement is not uniform.
Keywords: normalization; harmonization; conformity assessment system; economic development; product